Keefektifan Konseling Kelompok Cognitive Behavior Teknik Cognitive Restructuring untuk Mereduksi Kecanduan Media Sosial Peserta Didik Kelas XI MAN 3 Bantul - Afna Afifah; Akhmad Fajar Prasetya (STIKes Ibnu Sina Ajibarang, 2025)
The phenomenon underlying this study indicates social media addiction in class XI students of MAN 3 Bantul. This study aims to reduce social media addiction through cognitive behavior group counseling services using cognitive restructuring techniques. This study uses the pre-experimental design one group pretest-posttest method. The results of the study showed a decrease in social media addiction scores in students. This is evidenced by the results of the paired sample t-test with a significance value (2-tailed) of 0.004, which means less than 0.05. It can be concluded from these results that cognitive behavior group counseling using cognitive restructuring techniques is effective in reducing social media addiction in class XI students of MAN 3 Bantul. Changes in behavior are shown from the results of the posttest after participating in cognitive behavior group counseling services using cognitive restructuring techniques, with a decrease in the frequency of social media use, self-awareness and changes in more rational thought patterns.